Motivasi Minat Budaya Membaca dan Bercerita pada Siswa Melalui Program Gerakan Literasi dalam Meningkatkan Intelektual di MI Guppi Serang - Pupi Dwi Hayati; Engkay Sukaesih (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2023)
The aim of this research is to analyze the motivation for students' cultural interest in reading and telling stories through the literacy movement program in improving students' intellectual abilities at MI Guppi Serang. This research uses qualitative research. Participants in this research were 131 MI GUPPI Serang students, Karangreja District, Purbalingga Regency, Central Java in grades 4-6 MI. Data collection techniques use observation, interviews and documentation. The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, and data verification. The results of the research show that students at MI GUPPI have good intellectual abilities after the existence of a culture of reading and telling stories through the literacy movement program. There needs to be collaborative efforts between schools, parents and the community in increasing students' motivation to read and tell stories, the most important obstacle in this effort. Increasing motivation for students' interest in reading is the lack of reference and reading sources